Factors Influencing the Level of Community Knowledge About the Family Planning Program in Eti Village, West Seram District, West Seram Regency - Kamalatu, Yesty; Lasaiba, Mohammad Amin; Sihasale, Daniel Anthoni (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2022)
Eucalyptus (Melaleuca leucadendron Linn.) is an essential oil-producing plant with good prospects for development. This study aimed to examine the fulfillment of the needs of eucalyptus oil farming families. This research was conducted in Wainibe Village, Fenaleisela District, Buru Regency, with a simple random sampling of 30 farmers. Data were analyzed descriptively, while quantitative data were analyzed using frequency tables. The study results show that most of the respondents have capital, a supportive workforce, and good marketing locations in the local market. Most of the income ranges outside the region from IDR 2,000,000 to 4,000,000. The respondents' food needs are fulfilled, and the food and clothing needs of the respondents can be fulfilled. The needs of the respondent's board can be fulfilled by owning a house. The fulfillment of educational and health needs is also fulfilled.